Comparison of the dosimetric accuracy of proton breast treatment plans delivered with SGRT and CBCT setups. Issue 9 (20th July 2021) - MacFarlane, Michael J.; Jiang, Kai; Mundis, Michelle; Nichols, Elizabeth; Gopal, Arun; Chen, Shifeng; Biswal, Nrusingh C.
Abstract: Purpose: To compare the dosimetric accuracy of surface‐guided radiation therapy (SGRT) and cone‐beam computed tomography (CBCT) setups in proton breast treatment plans. Methods: Data from 30 patients were retrospectively analyzed in this IRB‐approved study. Patients were prescribed 4256–5040 cGy in 16–28 fractions. CBCT and AlignRT (SGRT; Vision RT Ltd.) were used for treatment setup during the first three fractions, then daily AlignRT and weekly CBCT thereafter. Each patient underwent a quality assurance CT (QA‐CT) scan midway through the treatment course to assess anatomical and dosimetric changes. To emulate the SGRT and CBCT setups during treatment, the planning CT and QA‐CT images were registered in two ways: (1) by registering the volume within the CTs covered by the CBCT field of view; and (2) by contouring and registering the surface surveyed by the AlignRT system. The original plan was copied onto these two datasets and the dose was recalculated. The clinical treatment volume (CTV): V95% ; heart: V25Gy, V15Gy, and mean dose; and ipsilateral lung: V20Gy, V10Gy, and V5Gy, were recorded. Multi and univariate analyses of variance were performed to assess the differences in dose metric values between the planning CT and the SGRT and CBCT setups. Results: The CTV V95% and lung V20Gy, V10Gy, and V5Gy dose metrics were all significantly ( p < 0.01) lower on the QA‐CT in both the CBCT and SGRT setup. The differences were not clinically significant and were, on average, 1.4–1.6% lower for CTV V95% and 1.8%–6.0% lower for the lung dose metrics. When comparing the lung and CTV V95% dose metrics between the CBCT and SGRT setups, no significant difference was observed. This indicates that the SGRT setup provides similar dosimetric accuracy as CBCT. Conclusion: This study supports the daily use of SGRT systems for the accurate dose delivery of proton breast treatment plans.